Composite dispersion liquid based on carbon nanofibers as well as preparation method and application of composite dispersion liquid

By mixing the carbon nano fiber -Coona+carbon nanomani fiber and cellulose, it is emulsified, grinded, and average to form a stable composite decentralized liquid, solved the problem of poor stability of MFC and BC decentralized liquids, and achieved long-term stable dispersing decentralized decentralization Effect.

CN119352327APending Publication Date: 2025-01-24GUILIN QIHONG TECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411505984.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The stability of microfibrotic cellulose (MFC) and bacterial cellulose (BC) is easily affected by environmental factors, pH and microbial effects, resulting in water absorption and expansion during dispersion, affecting the stability of the dispersion.

Method used

By mixing the carbon nano fiber, cellulose and solvents of the branch-Coona+, formation of cellulose/carbon nanofiber decentralized solution, and through the steps such as emulsification, grinding, and homogeneity, use the dual-electrical layer of carbon nanoplasm fiber Stable fiber dispersion.

Benefits of technology

The long-term stability of the composite dispersion based on carbon nanofibers was achieved, the problem of poor dispersion stability of MFC and BC dispersions was solved, and excellent stability was still maintained after 60 days.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352327A_ABST
    Figure CN119352327A_ABST
Patent Text Reader

Abstract

The invention provides a carbon nanofiber as well as a preparation method and application thereof, and belongs to the technical field of preparation of composite slurry. The preparation method comprises the following steps: firstly, preparing a cellulose / carbon nanofiber dispersion liquid, and enabling-COONa < + > groups in carbon nanofibers grafted with-COONa < + > to form repulsive interaction of double electric layers, so that CNF has amphipathy and can form hydrophobic interaction with a hydrophobic carbon material; in addition, the carbon nanofibers grafted with the-COONa < + > can be wound with the cellulose. Therefore, the-COONa < + >-grafted carbon nanofibers can utilize the mutual repulsion and steric hindrance effects of static electricity of formed double electric layers, so that the cellulose can be stably dispersed in a solvent phase; the cellulose / carbon nanofiber dispersion liquid can be dispersed step by step by sequentially emulsifying, grinding and homogenizing, so that the composite dispersion liquid based on the carbon nanofibers can be stable for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite slurry preparation, and in particular to a composite dispersion liquid based on carbon nanofibers, and a preparation method and application thereof. Background Art

[0002] Compared with the problem of long natural degradation time of plastic packaging materials, paper packaging materials have the advantages of being green and environmentally friendly and having a short natural degradation time, and have attracted much attention from researchers. Pulp molding products are made by processing and mixing fiber raw materials into a slurry with a certain concentration ratio. According to product design and customized molds, they are formed by vacuum adsorption and the principle of in-mold drying is used to form environmentally friendly paper products of different types and uses. However, the quality of raw materials has a direct impact on the quality of pulp molded products. If the quality of raw materials is unstable, the shrinkage ratio of the product after drying will not be consistent with the original design process, resulting in a high product breakage rate. Therefore, obtaining high-quality pulp molded products requires good stability of the raw materials.

[0003] Microfibrillated cellulose (MFC) is a fibrous nanomaterial obtained by mechanical grinding of wood pulp, which can be used to prepare pulp molding products. However, the stability of MFC is affected by environmental factors. First, the ambient temperature and humidity have a significant effect on the stability of cellulose. Under high temperature and high humidity, cellulose easily absorbs water, causing structural changes, thus affecting its stability. Secondly, pH is also an important factor affecting the stability of cellulose. Strong acid or strong alkaline environment will destroy the hydrogen bond structure of cellulose, leading to cellulose degradation and instability. In addition, microbial action will also affect the stability of cellulose. Some microorganisms can secrete cellulase to decompose cellulose into oligosaccharides or monosaccharides, thereby reducing its stability. Bacterial cellulose (BC) refers to a general term for cellulose synthesized by certain microorganisms in the genera Acetobacter, Agrobacterium, Rhizobium and Sarcina under different conditions. It has a wide range of applications in the food field, cosmetics field, medical field and papermaking industry. However, the high water holding capacity and high air permeability of BC make it easy to absorb water and swell during the dispersion process, which has an adverse effect on dispersion. Therefore, both MFC and BC have the problem of stability that needs to be improved.

[0004] Therefore, there is an urgent need to provide a method for preparing a MFC and / or BC dispersion with high stability. Summary of the invention

[0005] The purpose of the present invention is to provide a composite dispersion liquid based on carbon nanofibers and a preparation method and application thereof. The composite dispersion liquid based on carbon nanofibers prepared by the present invention has excellent stability.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0008] (1) Grafting -COONa + Mixing carbon nanofibers, cellulose and a solvent to obtain a cellulose / carbon nanofiber dispersion; the cellulose includes nanocellulose and / or bacterial cellulose;

[0009] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is emulsified, ground and homogenized in sequence to obtain a composite dispersion based on carbon nanofibers.

[0010] Preferably, in step (1), -COONa is grafted + The length of the carbon nanofibers is 80 to 300 nm, and the grafted -COONa + The aspect ratio of the carbon nanofibers is 1:500-1000.

[0011] Preferably, in step (1), -COONa is grafted + The preparation method of carbon nanofibers comprises: mixing plant fibers, sodium hydroxide solution and anhydrous ethanol, carrying out grafting reaction to obtain modified fibers; dissociating and crushing the modified fibers to obtain grafted-COONa + of carbon nanofibers.

[0012] Preferably, the solvent in step (1) comprises water, ethanol or N-methylpyrrolidone.

[0013] Preferably, in step (1), the diameter of the bacterial cellulose is 50-100 nm and the length is 10-20 μm.

[0014] Preferably, in step (1), -COONa is grafted + The mass of carbon nanofibers accounts for the grafted-COONa + The total mass ratio of carbon nanofibers to cellulose is 1 to 80%.

[0015] Preferably, the mass concentration of the cellulose / carbon nanofiber dispersion in step (1) is 0.01-30%.

[0016] Preferably, the rotation speeds of emulsification and grinding in step (2) are independently 500 to 5000 r / min.

[0017] The present invention also provides a composite dispersion based on carbon nanofibers prepared by the preparation method described in the above technical solution.

[0018] The present invention also provides the use of the carbon nanofiber-based composite dispersion described in the above technical solution in the preparation of pulp molding products.

[0019] The present invention provides a method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps: grafting -COONa + The carbon nanofibers, cellulose and solvent are mixed to obtain a cellulose / carbon nanofiber dispersion; the cellulose includes nanocellulose and / or bacterial cellulose; the cellulose / carbon nanofiber dispersion is sequentially emulsified, ground and homogenized to obtain a composite dispersion based on carbon nanofibers. The present invention first prepares a cellulose / carbon nanofiber dispersion, grafts -COONa + -COONa in carbon nanofibers + The groups can form a repulsive double layer, making CNF amphiphilic and able to form hydrophobic interactions with hydrophobic carbon materials; and grafted -COONa + The carbon nanofibers can also be entangled with cellulose. + The carbon nanofibers can utilize the electrostatic mutual repulsion and steric hindrance of the formed double electric layer to stably disperse cellulose in the solvent phase; the present invention can disperse the cellulose / carbon nanofiber dispersion step by step by sequentially emulsifying, grinding and homogenizing, so that the composite dispersion based on carbon nanofibers can be stable for a long time. The results of the embodiment show that the composite dispersion based on carbon nanofibers prepared by the method of the present invention still has excellent stability after being placed for 60 days, which can solve the problem of poor dispersion stability of nanocellulose and bacterial cellulose dispersions. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM image of the composite dispersion based on carbon nanofibers prepared in Example 1 of the present invention;

[0021] Figure 2 This is a SEM image of the composite dispersion based on carbon nanofibers prepared in Example 2 of the present invention;

[0022] Figure 3 This is a SEM image of the composite dispersion based on carbon nanofibers prepared in Example 3 of the present invention;

[0023] Figure 4 This is a SEM image of the composite dispersion based on carbon nanofibers prepared in Example 6 of the present invention;

[0024] Figure 5 This is a SEM image of the composite dispersion based on carbon nanofibers prepared in Example 7 of the present invention;

[0025] Figure 6 This is a SEM image of the composite dispersion based on carbon nanofibers prepared in Example 8 of the present invention;

[0026] Figure 7This is a SEM image of the CNF dispersion prepared in Comparative Example 1 of the present invention;

[0027] Figure 8 This is a SEM image of the MFC dispersion prepared in Comparative Example 2 of the present invention;

[0028] Fig. 9 The photos are of the composite dispersions based on carbon nanofibers prepared in Examples 1 to 5 of the present invention and the MFC dispersion prepared in Comparative Example 2 after being left to stand for one day;

[0029] Fig.10 The photos are of the composite dispersions based on carbon nanofibers prepared in Examples 1 to 5 of the present invention and the MFC dispersion prepared in Comparative Example 2 after being left to stand for 20 days;

[0030] Fig.11 The photos are of the composite dispersions based on carbon nanofibers prepared in Examples 6 to 10 of the present invention and the BC dispersion prepared in Comparative Example 3 after being left to stand for one day;

[0031] Fig.12 These are photos of the carbon nanofiber-based composite dispersions prepared in Examples 6 to 10 of the present invention and the BC dispersion prepared in Comparative Example 3 after standing for 20 days. DETAILED DESCRIPTION

[0032] The present invention provides a method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0033] (1) Grafting -COONa + Mixing carbon nanofibers, cellulose and a solvent to obtain a cellulose / carbon nanofiber dispersion; the cellulose includes nanocellulose and / or bacterial cellulose;

[0034] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is emulsified, ground and homogenized in sequence to obtain a composite dispersion based on carbon nanofibers.

[0035] The present invention grafts -COONa + The carbon nanofibers, cellulose and a solvent are mixed to obtain a cellulose / carbon nanofiber dispersion.

[0036] In the present invention, the grafted -COONa + The length of the carbon nanofiber is preferably 80 to 300 nm, more preferably 120 to 230 nm; the aspect ratio of the carbon nanofiber grafted with -COONa+ is preferably 1:500 to 1000, more preferably 1:600 ​​to 800. + The carbon nanofibers have a larger aspect ratio, which is more conducive to entanglement with cellulose, thereby improving the dispersion stability of cellulose in the solvent.

[0037] In the present invention, the grafted -COONa + The method for preparing carbon nanofibers preferably comprises: mixing plant fibers, sodium hydroxide solution and anhydrous ethanol, carrying out a grafting reaction to obtain modified fibers; and dissociating and crushing the modified fibers to obtain carbon nanofibers grafted with -COONa+.

[0038] The present invention preferably mixes plant fiber, sodium hydroxide solution and anhydrous ethanol to carry out grafting reaction to obtain modified fiber.

[0039] In the present invention, the plant fiber is preferably sisal fiber. The present invention does not specifically limit the preparation method of the sisal fiber, and any conventional preparation method can be used. In an embodiment of the present invention, the preparation method of the sisal fiber can be: chop the sisal into pieces, weigh 30.0g and add it to a 500mL high-pressure reactor; weigh 12.0gNaOH, 12.0g Na2S·9H2O and 300mL of deionized water to make a solution, and add it to the reactor; place the reactor in an oven and react at 170°C for 3h. Wash and dry after the reaction is completed. Weigh 20.0g of the dried sample, weigh 6.0g NaClO2, 5.0mL glacial acetic acid and 650mL of deionized water to make a solution, mix and react at 80°C for 2h, filter, wash and dry to obtain sisal fiber.

[0040] In the present invention, the mass concentration of the sodium hydroxide solution is preferably 7-8wt%, more preferably 7.7wt%.

[0041] In the present invention, when the mass concentration of the sodium hydroxide solution is 7-8wt%, the ratio of the mass of the plant fiber, the volume of the sodium hydroxide solution and the volume of anhydrous ethanol is preferably (20-25) g: (70-75) mL: (450-500) mL, and more preferably 24 g: 72 mL: 480 mL.

[0042] In the present invention, the method of mixing the plant fiber, the sodium hydroxide solution and the anhydrous ethanol is preferably: soaking the plant fiber in the sodium hydroxide solution for 10 to 30 minutes, then adding the anhydrous ethanol and stirring evenly.

[0043] In the present invention, the temperature of the grafting reaction is preferably 65 to 75° C., more preferably 71 to 75° C.; the time of the grafting reaction is preferably 3 to 5 hours, more preferably 4 to 5 hours.

[0044] In the present invention, the product after the grafting reaction is preferably washed to obtain modified fibers. The present invention has no special limitation on the washing operation, as long as the unreacted impurities can be fully removed. In an embodiment of the present invention, the washing agent can be deionized water.

[0045] After obtaining the modified fiber, the present invention preferably mixes the modified fiber with deionized water, dissociates and breaks it, and obtains the grafted -COONa + of carbon nanofibers.

[0046] In the present invention, the slurry concentration after the modified fiber is mixed with deionized water is preferably 0.5-0.8 wt%, more preferably 0.6 wt%.

[0047] In the present invention, the dissociation and fragmentation method is preferably: adjusting the slurry after the modified fiber is mixed with deionized water to a transparent jelly-like product, filtering the transparent jelly-like product with a 500-mesh filter cloth, adding deionized water to the filter residue to adjust the solid content concentration to 0.2wt%, taking the upper layer of liquid after centrifugation, and concentrating and drying to obtain the grafted-COONa + of carbon nanofibers.

[0048] The present invention can introduce -COONa on carbon nanofibers by adopting the above method. + The groups enable the carbon nanofibers to disperse the cellulose.

[0049] In the present invention, the cellulose includes nanocellulose and / or bacterial cellulose.

[0050] The present invention has no special limitation on the source of the nanocellulose, and conventional commercial products can be used. In the present invention, the source of the nanocellulose is preferably Guilin Qihong Technology Co., Ltd.

[0051] In the present invention, the diameter of the bacterial cellulose is preferably 50-100 nm, more preferably 50-80 nm; the length of the bacterial cellulose is preferably 10-20 μm, more preferably 10-15 μm. The present invention has no special restrictions on the source of the nanocellulose, and conventional commercial products can be used. In the present invention, the source of the nanocellulose is preferably Guilin Qihong Technology Co., Ltd.

[0052] In the present invention, the solvent preferably includes water, ethanol or N-methylpyrrolidone, more preferably water. In the present invention, the solvent is a common dispersant in cellulose applications. When the present invention uses the above solvent, the prepared composite dispersion based on carbon nanofibers can be directly used.

[0053] In the present invention, the grafted -COONa + The quality of carbon nanofibers and grafted-COONa +The total mass ratio of carbon nanofibers to cellulose is preferably (1-80):100, expressed as 1%-80%; more preferably (1-50):100, expressed as 1%-50%. In the embodiment of the present invention, the grafted -COONa + The quality of carbon nanofibers and grafted-COONa + The total mass ratio of the carbon nanofibers to the cellulose can be 1:100, 5:100, 10:100, 20:100 or 50:100.

[0054] In the present invention, the mass concentration of the cellulose / carbon nanofiber dispersion is preferably 0.01-30%, more preferably 0.1-5%. The present invention controls the mass concentration of the cellulose / carbon nanofiber dispersion within the above range, which is more conducive to the full dispersion of the composite dispersion based on carbon nanofibers.

[0055] The present invention is to graft -COONa + The method for mixing the carbon nanofibers, cellulose and solvent is not particularly limited, and a conventional mixing method can be used to mix the components uniformly. + The method for mixing the carbon nanofibers, cellulose and solvent is preferably ultrasound. In an embodiment of the present invention, the power of the ultrasound can be 3000W; the time of the ultrasound is preferably 20s to 1min, more preferably 30s to 1min.

[0056] After obtaining the cellulose / carbon nanofiber dispersion, the present invention sequentially emulsifies, grinds and homogenizes the cellulose / carbon nanofiber dispersion to obtain a composite dispersion based on carbon nanofibers.

[0057] In the present invention, the rotation speed of the emulsification is preferably 500 to 5000 r / min, more preferably 1000 to 4000 r / min; the emulsification time is preferably 2 to 20 min, more preferably 5 to 15 min. The present invention can further disperse the cellulose / carbon nanofiber dispersion by emulsification. The present invention has no special limitation on the emulsification device, and any conventional emulsification device can be used.

[0058] In the present invention, the grinding speed is preferably 500 to 5000 r / min, more preferably 1000 to 4000 r / min; the grinding time is preferably 30 to 180 min, more preferably 60 to 120 min. The present invention can promote the grafting of -COONa by using the shear force of grinding. +The carbon nanofibers and cellulose are fully contacted and entangled, thereby promoting further dispersion of the cellulose / carbon nanofiber dispersion. The present invention has no special limitation on the grinding device, and any conventional grinding device can be used. In an embodiment of the present invention, the grinding device can be a grinder.

[0059] In the present invention, the homogenizer is preferably a high-pressure homogenizer, and the pressure of the high-pressure homogenizer is preferably 20 to 100 MPa, more preferably 50 to 100 MPa. The present invention can break up the colloid in the ground cellulose / carbon nanofiber dispersion by high-speed shearing with mechanical force through homogenization, and has a good dispersion effect. In food processing, homogenization can refine the material and make the whole system more stable.

[0060] The preparation method provided by the present invention comprises first preparing a cellulose / carbon nanofiber dispersion, grafting -COONa + The carbon nanofibers can utilize the electrostatic mutual repulsion and steric hindrance of the formed double electric layer to enable cellulose to be stably dispersed in the solvent phase; the present invention can disperse the cellulose / carbon nanofiber dispersion step by step by sequentially performing emulsification, grinding and homogenization, so that the composite dispersion based on carbon nanofibers can be stable for a long time.

[0061] The present invention also provides a composite dispersion based on carbon nanofibers prepared by the preparation method described in the above technical solution.

[0062] In the present invention, the composite dispersion liquid based on carbon nanofibers can maintain dispersion stability after being left to stand for more than 20 days. The present invention provides a preparation method that can make the composite dispersion liquid of carbon nanofibers stable for a long time, and thus the composite dispersion liquid based on carbon nanofibers can still exist stably after being left to stand for a long time without stratification and floccules.

[0063] The present invention also provides the use of the carbon nanofiber-based composite dispersion described in the above technical solution in the preparation of pulp molding products.

[0064] The present invention has no special limitation on the application method of the carbon nanofiber-based composite dispersion in the preparation of pulp molded products, and any conventional method for preparing pulp molded products may be used.

[0065] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0066] Example 1

[0067] A method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0068] (1) Grafting -COONa + The preparation method of carbon nanofiber is as follows: cut sisal into pieces, weigh 30.0g and add it to a 500mL high-pressure reactor; weigh 12.0gNaOH, 12.0gNa2S·9H2O and 300mL of deionized water to make a solution, add it to the reactor; place the reactor in an oven and react at 170°C for 3h. After the reaction is completed, wash and dry. Weigh 20.0g of the dried sample, weigh 6.0gNaClO2, 5.0mL of glacial acetic acid and 650mL of deionized water to make a solution, mix them and react at 80°C for 2h, filter, wash and dry to obtain sisal fiber; weigh 24.0g of sisal fiber, soak it in 72mLNaOH solution (7.7wt%) at room temperature for 30min, and press it hard to make it completely soaked. Transfer it to a 1000mL three-necked flask, add 480mL of anhydrous ethanol, mix well and react at 71°C for 4h. The product was filtered and washed with deionized water. It was mixed with a certain amount of deionized water to make its solid content 0.6wt%. The mixture was then stirred at the highest speed of the high-speed stirrer for 10min (stirred twice, each time for 5min) to obtain a transparent jelly-like product. The product was squeezed and filtered once with a 500-mesh filter cloth, and then the concentration was adjusted to 0.2wt% with deionized water. It was centrifuged at 12000rpm for 8min, and 80% of the liquid in the upper part of the centrifuge tube was concentrated to obtain CNF dispersion, which was dried to obtain grafted-COONa + The carbon nanofibers are denoted as CNF;

[0069] Nanocellulose, denoted as MFC;

[0070] Dispersing CNF and water by ultrasonic method to obtain a CNF dispersion with a concentration of 1%;

[0071] Ultrasonic dispersion of MFC and water was performed to obtain a 0.5% MFC dispersion;

[0072] According to the mass of CNF accounting for 1% of the total mass of MFC and CNF, the CNF dispersion and the MFC dispersion are ultrasonically dispersed to obtain a cellulose / carbon nanofiber dispersion;

[0073] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a composite dispersion based on carbon nanofibers, recorded as MFC+1% CNF.

[0074] Example 2

[0075] A method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0076] (1) ultrasonically dispersing CNF and water to obtain a CNF dispersion with a concentration of 1%;

[0077] Ultrasonic dispersion of MFC and water was performed to obtain a 0.5% MFC dispersion;

[0078] According to the mass of CNF accounting for 10% of the total mass of MFC and CNF, the CNF dispersion and the MFC dispersion are ultrasonically dispersed;

[0079] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a composite dispersion based on carbon nanofibers, recorded as MFC+10% CNF.

[0080] Example 3

[0081] A method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0082] (1) ultrasonically dispersing CNF and water to obtain a CNF dispersion with a concentration of 1%;

[0083] Ultrasonic dispersion of MFC and water was performed to obtain a 0.5% MFC dispersion;

[0084] According to the mass of CNF accounting for 50% of the total mass of MFC and CNF, the CNF dispersion and the MFC dispersion are ultrasonically dispersed;

[0085] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a composite dispersion based on carbon nanofibers, recorded as MFC+50% CNF.

[0086] Example 4

[0087] A method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0088] (1) ultrasonically dispersing CNF and water to obtain a CNF dispersion with a concentration of 1%;

[0089] Ultrasonic dispersion of MFC and water was performed to obtain a 0.5% MFC dispersion;

[0090] According to the mass of CNF accounting for 5% of the total mass of MFC and CNF, the CNF dispersion and the MFC dispersion are ultrasonically dispersed;

[0091] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a composite dispersion based on carbon nanofibers, recorded as MFC+5% CNF.

[0092] Example 5

[0093] A method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0094] (1) ultrasonically dispersing CNF and water to obtain a CNF dispersion with a concentration of 1%;

[0095] Ultrasonic dispersion of MFC and water was performed to obtain a 0.5% MFC dispersion;

[0096] According to the mass of CNF accounting for 20% of the total mass of MFC and CNF, the CNF dispersion and the MFC dispersion are ultrasonically dispersed;

[0097] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a composite dispersion based on carbon nanofibers, recorded as MFC+20% CNF.

[0098] Example 6

[0099] A method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0100] (1) The diameter of bacterial cellulose is 50-100 nm and the length is 10-20 μm (Guilin Qihong Technology Co., Ltd.); the obtained nanocellulose is denoted as BC;

[0101] Dispersing CNF and water by ultrasonic method to obtain a CNF dispersion with a concentration of 1%;

[0102] Ultrasonic dispersion of BC and water was performed to obtain a BC dispersion with a concentration of 0.5%;

[0103] According to the mass of CNF accounting for 1% of the total mass of BC and CNF, the CNF dispersion and the MFC dispersion are ultrasonically dispersed;

[0104] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a composite dispersion based on carbon nanofibers, recorded as BC+1% CNF.

[0105] Example 7

[0106] A method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0107] (1) ultrasonically dispersing CNF and water to obtain a CNF dispersion with a concentration of 1%;

[0108] Ultrasonic dispersion of BC and water was performed to obtain a BC dispersion with a concentration of 0.5%;

[0109] According to the mass of CNF accounting for 10% of the total mass of BC and CNF, the CNF dispersion and the MFC dispersion are ultrasonically dispersed;

[0110] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a composite dispersion based on carbon nanofibers, recorded as BC+10% CNF.

[0111] Example 8

[0112] A method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0113] (1) ultrasonically dispersing CNF and water to obtain a CNF dispersion with a concentration of 1%;

[0114] Ultrasonic dispersion of BC and water was performed to obtain a BC dispersion with a concentration of 0.5%;

[0115] According to the mass of CNF accounting for 50% of the total mass of BC and CNF, the CNF dispersion and the MFC dispersion are ultrasonically dispersed;

[0116] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a composite dispersion based on carbon nanofibers, recorded as BC+50% CNF.

[0117] Example 9

[0118] A method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0119] (1) ultrasonically dispersing CNF and water to obtain a CNF dispersion with a concentration of 1%;

[0120] Ultrasonic dispersion of BC and water was performed to obtain a BC dispersion with a concentration of 0.5%;

[0121] According to the mass of CNF accounting for 5% of the total mass of BC and CNF, the CNF dispersion and the MFC dispersion are ultrasonically dispersed;

[0122] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a composite dispersion based on carbon nanofibers, recorded as BC+5% CNF.

[0123] Example 10

[0124] A method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps:

[0125] (1) ultrasonically dispersing CNF and water to obtain a CNF dispersion with a concentration of 1%;

[0126] Ultrasonic dispersion of BC and water was performed to obtain a BC dispersion with a concentration of 0.5%;

[0127] According to the mass of CNF accounting for 20% of the total mass of BC and CNF, the CNF dispersion and the MFC dispersion are ultrasonically dispersed;

[0128] (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a composite dispersion based on carbon nanofibers, recorded as BC+20% CNF.

[0129] Comparative Example 1

[0130] A method for preparing a dispersion of carbon nanofibers, comprising the following steps:

[0131] (1) ultrasonically dispersing CNF and water to obtain a CNF dispersion with a concentration of 1%;

[0132] (2) The CNF dispersion obtained in step (1) is first emulsified at a speed of 1000 r / min for 15 min, then ground in a grinder at a speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a CNF dispersion, recorded as CNF.

[0133] Comparative Example 2

[0134] A method for preparing an MFC dispersion, comprising the following steps:

[0135] (1) ultrasonically dispersing MFC and water to obtain an initial MFC dispersion with a concentration of 0.5%;

[0136] (2) The initial MFC dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain an MFC dispersion, which is recorded as MFC.

[0137] Comparative Example 3

[0138] A method for preparing a BC dispersion, comprising the following steps:

[0139] (1) ultrasonically dispersing BC and water to obtain an initial BC dispersion with a concentration of 0.5%;

[0140] (2) The BC initial dispersion obtained in step (1) is first emulsified at a rotation speed of 1000 r / min for 15 min, then ground in a grinder at a rotation speed of 1000 r / min for 60 min, and finally homogenized in a high-pressure homogenizer at 100 MPa to obtain a BC dispersion, recorded as BC.

[0141] Test Example 1

[0142] The composite dispersions based on carbon nanofibers prepared in Examples 1 to 3 and Examples 6 to 8, the CNF dispersion prepared in Comparative Example 1, and the MFC dispersion prepared in Comparative Example 2 were tested by scanning electron microscopy, and the SEM images of MFC+1% CNF were obtained as shown in FIG. Figure 1 As shown; the SEM image of MFC+10% CNF is as shown Figure 2 As shown; the SEM image of MFC+50%CNF is as shown Figure 3 As shown; SEM image of BC+1% CNF is shown Figure 4 As shown; SEM image of BC+10% CNF is shown Figure 5 As shown; SEM image of BC+50%CNF is shown Figure 6 As shown; the SEM image of CNF is as follows Figure 7As shown; the SEM image of MFC is as follows Figure 8 shown.

[0143] from Figure 7 and 8 It can be seen that both CNF and MFC show obvious agglomeration in water. Figures 1 to 6 It can be seen that as the amount of CNF added increases, the dispersibility of the composite dispersion based on carbon nanofibers is improved. This is because the present invention first prepares the cellulose / carbon nanofiber dispersion, and the carbon nanofibers grafted with -COONa+ can utilize the electrostatic mutual repulsion and steric hindrance of the formed double electric layer to enable cellulose to be stably dispersed in the solvent phase.

[0144] Test Example 2

[0145] The photos of the carbon nanofiber-based composite dispersions prepared in Examples 1 to 5 and the MFC dispersion prepared in Comparative Example 2 after standing for one day are shown in FIG. Fig. 9 As shown, the photos taken after 20 days of standing Fig.10 As shown; the composite dispersion based on carbon nanofibers prepared in Examples 6 to 10 and the BC dispersion prepared in Comparative Example 3 were left to stand for 1 day. Fig.11 As shown, the photos taken after 20 days of standing Fig.12 As shown. Figures 9 to 12 It can be seen that the carbon nanofiber-based composite dispersions prepared in Examples 1 to 10 have no significant difference from the dispersions left standing for 1 day after standing for 20 days, while the MFC dispersion and the BC dispersion showed flocculation and precipitation after standing for 20 days. This shows that the method provided by the present invention can obtain a composite dispersion with excellent stability and improve the dispersion stability of MFC and BC in water.

[0146] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a composite dispersion based on carbon nanofibers, comprising the following steps: (1) Grafting -COONa + Mixing carbon nanofibers, cellulose and a solvent to obtain a cellulose / carbon nanofiber dispersion; the cellulose includes nanocellulose and / or bacterial cellulose; (2) The cellulose / carbon nanofiber dispersion obtained in step (1) is emulsified, ground and homogenized in sequence to obtain a composite dispersion based on carbon nanofibers.

2. The preparation method according to claim 1, characterized in that: In the step (1), -COONa is grafted + The length of the carbon nanofibers is 80 to 300 nm, and the grafted -COONa + The aspect ratio of the carbon nanofibers is 1:500-1000.

3. The preparation method according to claim 1 or 2, characterized in that: In the step (1), -COONa is grafted + The preparation method of carbon nanofibers comprises: mixing plant fibers, sodium hydroxide solution and anhydrous ethanol, carrying out grafting reaction to obtain modified fibers; dissociating and crushing the modified fibers to obtain grafted-COONa + of carbon nanofibers.

4. The preparation method according to claim 1, characterized in that: The solvent in step (1) includes water, ethanol or N-methylpyrrolidone.

5. The preparation method according to claim 1, characterized in that: In the step (1), the diameter of the bacterial cellulose is 50 to 100 nm and the length is 10 to 20 μm.

6. The preparation method according to claim 1, characterized in that: In the step (1), -COONa is grafted + The mass of carbon nanofibers accounts for the grafted-COONa + 1 to 80% of the total mass of carbon nanofibers and cellulose.

7. The preparation method according to claim 1, characterized in that: The mass concentration of the cellulose / carbon nanofiber dispersion in step (1) is 0.01-30%.

8. The preparation method according to claim 1, characterized in that: In the step (2), the rotation speeds of emulsification and grinding are independently 500 to 5000 r / min.

9. A composite dispersion based on carbon nanofibers prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the carbon nanofiber-based composite dispersion according to claim 9 in the preparation of pulp molding products.

Citation Information

Patent Citations

  • Method for preparing submicron or nanometer cellulose by mechanical force

    CN104311675A

  • Method for stably dispersing metal oxide nano-particles in aqueous phase

    CN107311218A

  • Modified carboxymethylated cellulose nanofiber dispersion and method for manufacturing same

    CN108602896A

  • Modification method for plant fiber or nanocellulose

    CN109810255A

  • Method for manufacturing carboxymethylated cellulose nanofiber

    CN111511770A